PENDAYAGUNAAN KARUNIA-KARUNIA ROH KUDUS BERDASARKAN 1 KORINTUS 12:1-12 DALAM MENINGKATKAN PERTUMBUHAN GEREJA - Herika Herika; Rudyanto Chandra Saputra; Gidion Gidion (STT Kristus Alfa Omega, 2020)
Gift-oriented ministry is one of the factors influencing church growth. a church that implements the utilization of the gifts of the Holy Spirit, then the church will experience church growth. Therefore, this study was conducted to determine whether there is a positive and significant influence between the utilization of the gifts of the Holy Spirit by God's servants on the growth of the church at Gereja Beth-El Tabernakel (GBT) Kristus Penebus Boyolali. This research uses quantitative methods and this research is in the form of a population and using a sample. Thus the hypothesis which states whether there is a positive and significant influence between the utilization of the gifts of the Holy Spirit by God's servants on the growth of the church at GBT Kristus Penebus Boyolali is accepted.